PROVISION OF A LIBRARY FOR THE VILLAGERS - Mawardini, Annisa (Universitas Djuanda, 2016)
Library is one of the reading places which has tremendous benefits to increase knowledge.Through reading, people can be more qualified. In its development, the need for readingrecognized as one of the basic human needs as a human right. However in its fulfillmentsometimes shows some of the things that are not satisfactory, such as the unavailability of alibrary or reading park, the limitations of the existing books and funds in the procurementlibrary, its influences to the lack of public interest in reading.